Low Dose of Lipopolysaccharide Pretreatment Preventing Subsequent Endotoxin-Induced Uveitis Is Associated with PI3K/AKT Pathway - Nan Zhang; Shuo Yu; Xinli Liu; Hong Lu (Journal of Immunology Research)
Purpose. To explore the effects of LPS pretreatment on endotoxin-induced uveitis and PI3K/AKT pathway. Methods. Endotoxin-induced uveitis was induced by a single subcutaneous injection of 200 μg LPS. For the endotoxin tolerance group, induction of EIU was preceded by daily subcutaneous injection of 0.1 mg/kg LPS for five days. Clinical scores were graded at 24 h after EIU under a slit lamp microscope. HE stain was performed to observe the histopathology. Aqueous humor TNF-α concentration was quantified with enzyme-linked immunosorbent assay. The expressions of PI3K and AKT were detected through Western blot analyses, and the activation of AKT was detected through immunofluorescence study. Results. Endotoxin tolerance produced suppressive effects by significantly reducing the inflammatory reaction of anterior segment of the rats as measured by slit lamp and histopathology. Low dose of LPS pretreatment significantly reduced TNF-α concentrations and the expressions of PI3K and AKT. Furthermore, the activation of AKT was also inhibited. Conclusions. LPS pretreatment can ameliorate endotoxin-induced uveitis in rats. This protection of endotoxin tolerance against EIU is associated with PI3K/AKT pathway by reducing level of TNF-α in the aqueous humor.